Soil Use Legacy as Driving Factor for Soil Erosion under Conservation Agriculture - Grahmann, Kathrin; Rubio, Valentina; Perez-Bidegain, Mario; Quincke, Juan Andrés (Frontiers in Environmental Science, 2022)
Water erosion can cause irreversible depletions in soil quality and crop productivity. The susceptibility of the soil to erosion is affected by current and historical management practices. Historical soil management practices like ploughing or subsoil loosening may lead to irreversible degradations of soils, which in turn increases soil erosion risk. Six “Wischmeier” plots under conservation agriculture, but with different historic treatments regarding soil use and management, were evaluated. These plots were installed in 1984 in Colonia del Sacramento, Uruguay on a Vertic Argiudoll. The objective of this study was to quantify how changes in soil quality, generated by different historical soil use and management over the last 35 years, contribute to current runoff and soil erosion in a cropping system under soil conservation practices using no-till, residue retention and cover crops. Considering differences in soil legacy effects of previous land use, plots were grouped in three treatments with contrasting historic index of agricultural intensification (IAI). The IAI was developed combining the duration of land use under agricultural production and the number and intensity of tillage activity resulting in the treatments: tillage with crop-pasture rotation (TIL_CP), no-tillage under several rotations (NT_Mix) and tillage with continuous cropping (TIL_CROP) with an increasing IAI of 3.5, 7.1 and 11.8, respectively. Rainfall events, runoff water and total, fixed and volatile solids were studied from 2017 to 2019. Soil physical (bulk density, penetration resistance, infiltration rate, aggregate stability), chemical (soil organic carbon (SOC), pH, phosphorous (P-Bray)) and biological properties (particulate organic matter (POM), potentially mineralizable nitrogen (PMN)) were assessed in 2019. Yearly average runoff amounted 209, 579 and 320 mm in 2017, 2018 and 2019, respectively. Yearly average soil losses were 233, 805 and 139 kg/ha with significant differences among years. The lowest soil losses were observed in TIL_CP (231, 615 and 146 kg/ha in 2017, 2018 and 2019, respectively) with lowest IAI of 3.5. Infiltration rate was the lowest in plots with highest IAI. Soil bulk density was highest (1.3 g/cm3) in plots with high IAI. SOC and PMN were lowest in TIL_CROP (3.0% SOC and 34 mg/kg PMN), holding the highest IAI of 11.8. Conservation agriculture minimized soil erosion losses in all plots and years, and erosion was much lower than the maximum tolerable threshold of 7,000 kg/ha for this particular soil. However, in historically intensively tilled and cropped soils, soil quality showed long-term adverse effects pointing towards a reduced resilience of the agricultural system.